2010
DOI: 10.4049/jimmunol.1000661
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Programmed Death-1 Defines CD8+CD122+ T Cells as Regulatory versus Memory T Cells

Abstract: Recent convincing data have shown that naturally occurring CD8+CD122+ T cells are also regulatory T cells. Paradoxically, CD8+CD122+ T cells have been well described as memory T cells. Given their critical role in tolerance versus long-term immunity, it is important to reconcile this profound dichotomy. In this study, we reported that CD8+CD122+ T cells contain both programmed death-1 (PD-1)− and PD-1+ populations. It was CD8+CD122+PD-1+ T cells, but not their PD-1− counterparts, that suppressed T cell respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
151
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(166 citation statements)
references
References 28 publications
(17 reference statements)
14
151
0
Order By: Relevance
“…In a number of experimental models in mice, CD8 + CD122 + T cells have been shown to be indispensable for sustaining immune homeostasis, including the induction of tolerance or suppression of autoimmunity (44,45,76,77). Insights arising from Cd122 -/-mouse studies support the functional role of this marker in maintaining immune homeostasis, as Cd122 -/-mice spontaneously develop severe hyperimmunity (44,45,78,79).…”
Section: Discussionmentioning
confidence: 99%
“…In a number of experimental models in mice, CD8 + CD122 + T cells have been shown to be indispensable for sustaining immune homeostasis, including the induction of tolerance or suppression of autoimmunity (44,45,76,77). Insights arising from Cd122 -/-mouse studies support the functional role of this marker in maintaining immune homeostasis, as Cd122 -/-mice spontaneously develop severe hyperimmunity (44,45,78,79).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 We have also found that CD8 1 CD122 1 T cells are memory-like Tregs that suppress allograft rejection in a murine model. 18 Hence, CD8 1 CD122 1 Tregs correspond to CD4 1 CD251 Tregs, given that CD122 is the b subunit of the IL-2 receptor on T cells, while CD25 is the a subunit of the same receptor, 19 which indicates that both subunits of the receptor are involved in Treg regulation. However, CD8 1 CD122 1 Tregs are recently emerging and relatively understudied in comparison with CD4 1 CD25 1 Tregs.…”
Section: Introductionmentioning
confidence: 99%
“…Certain surface phenotypes such as CD28 À [7], CD122 1 [8], CD8aa 1 [9,10], latencyassociated peptide (LAP) 1 [11] and restriction to the nonclassical MHCI molecule Qa-1 [12] have been linked with immunosuppressive functions of CD8 1 T cells. However, Foxp3 expression was either absent in these populations [8,9,[13][14][15], incongruent with the defining surface phenotype [11] or was not investigated specifically on a protein level [16]. Additionally, the isolation of viable CD8 1 Foxp3 1 populations was hampered by the nuclear localization of Foxp3 in conjunction with the occurrence of these cells at low numbers in nonmanipulated mice [2,17], rendering the identity and relevance of mouse CD8 1 Foxp3 1 T cells unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Certain surface phenotypes such as CD28 À [7], CD122 1 [8], CD8aa 1 [9, 10], latencyassociated peptide (LAP) 1 [11] and restriction to the nonclassical MHCI molecule Qa-1 [12] have been linked with immunosuppressive functions of CD8 1 T cells. However, Foxp3 expression was either absent in these populations [8,9,[13][14][15] …”
mentioning
confidence: 99%